Mainstreaming of PPKS Regulation in 2021 as Prevention Sexual Violence in Higher Education Environment: Pengarusutamaan Permen PPKS tahun 2021 sebagai Pencegahan Kekerasan Seksual di Lingkungan Perguruan Tinggi - Ari Darmastusi; Khairunnisa Simbolon; Astiwi Inayah (Ragom Jurnal Pengabdian Masyarakat, 2023)
The purpose of this community service is to provide knowledge, understanding and mastery of issues to the academic community at the University of Lampung regarding the Regulation of the Minister of Education on Sexual Violence (PPKS) in higher education institutions. This activity also aims to increase the awareness of the academic community about acts of sexual violence that occur on campus. This service activity is in the form of socialization through material presentation and discussion. It is carried out by conducting a pre-test and post-test to measure the knowledge of service participants about the 2021 PPKS Regulations. The longterm target to be achieved from this service is to increase student awareness of the issue of violence in the tertiary environment so that it can help prevent similar violence from happening in the future day